2014
DOI: 10.1590/s1415-47572014000200009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of founder mutations in hereditary breast cancer in Latin America

Abstract: Approximately 10% of all cancers are considered hereditary and are primarily caused by germline, high penetrance mutations in cancer predisposition genes. Although most cancer predisposition genes are considered molecularly heterogeneous, displaying hundreds of different disease-causing sequence alterations, founder mutations have been identified in certain populations. In some Latin American countries, founder mutations associated with increased risk of breast and other cancers have been described. This is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
28
0
4
Order By: Relevance
“…The clinical presentation of HBOC among Hispanic subpopulations is very similar to non-Hispanic cohorts [12, 17, 19, 21, 25, 3640]. Most studies reported that the majority of women that met inclusion criteria had BC diagnosed before age 50 (67.5%; range: 50.4–81.4%).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The clinical presentation of HBOC among Hispanic subpopulations is very similar to non-Hispanic cohorts [12, 17, 19, 21, 25, 3640]. Most studies reported that the majority of women that met inclusion criteria had BC diagnosed before age 50 (67.5%; range: 50.4–81.4%).…”
Section: Introductionmentioning
confidence: 87%
“…The majority of the studies reporting the prevalence of BRCA mutations in Hispanics have been performed on heterogeneous groups of Hispanic women from different countries, including: Mexico [911], Brazil [1214], Costa Rica [15], Chile [16, 17], Argentina [18], Peru [19], Colombia [20, 21], Venezuela [22], Bahamas [23], Cuba [24], and Puerto Rico [25] (Table 1). Recently, BRCA mutations in Latin American countries was published, which detailed the mutations found and how the prevalence changed from country to country [26].…”
Section: Introductionmentioning
confidence: 99%
“…Founder pathogenic variants in CRC predisposition genes appear to be less well studied when compared to breast cancer in several Latin American populations . We recently identified 16 internationally well‐known founder MMR variants in Brazil, Colombia, Argentina, Uruguay and Chile .…”
Section: Genetic Profile For Hereditary Crc: Lynch Syndromementioning
confidence: 99%
“…However, there are other mutations that are frequent in Latin America and uncommon in other populations, such as BRCA1 A1708E (10). Founder mutations have also been reported in Mexico ( BRCA1 ex9-12del) (28); in Colombia ( BRCA1 3450del4, A17082 and BRCA2 3034del4) (29, 30); and in Brazil ( BRCA1 5382insC and BRCA2 c.156_157insAlu) (31, 32). Although the majority of BRCA mutations consist of single base changes or deletions/insertions of small numbers of bases, large rearrangements of DNA segments have been reported twice as frequently in the Latin American populations.…”
Section: Introductionmentioning
confidence: 96%
“…The prevalence of other highly penetrant hereditary breast cancer genes, such as PTEN (Cowden’s Syndrome), TP53 (Li-Fraumeni syndrome), STK11 (Peutz-Jeghers syndrome) and CDH1 (Hereditary diffuse gastric cancer) is largely unknown in Latin America (32). An exception to this is the finding of the TP53 R337H founder mutation in Brazil.…”
Section: Introductionmentioning
confidence: 99%